2021
DOI: 10.31004/prepotif.v5i2.1882
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Risiko Ibu Dan Anak Balita Terhadap Stunting Di Wilayah Kerja Puskesmas Sangurara, Kecamatan Tatanga, Palu

Abstract: Stunting merupakan suatu kondisi dimana terjadi gagal tumbuh pada anak balita (bawah lima tahun) disebabkan oleh kekurangan gizi kronis, sehingga berpotensi mengakibatkan usia anak menjadi pendek. Berdasarkan data Dinkes Kota Palu Tahun 2020, menunjukkan bahwa Puskesmas Sangurara sebagai puskesmas yang memiliki kasus stunting cukup tinggi, yaitu sebanyak 373 (35,26%) kasus dibanding kasus penyakit lainnya. Tujuan penelitian untuk mengetahui tingkat risiko riwayat MP-ASI, usia ibu saat hamil, usia kehamilan ibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
1
1
Order By: Relevance
“…That is, the higher percentage of mothers who do not attend formal education, the lower prevalence of stunting in these locations. This is in contrast to research conducted by Azis et al (2021) which showed that risk factors for maternal education affect the incidence of stunting with a risk of 5,5 times. Tatu et al (2021) also analyzed the risk factors associated with the incidence of stunting, and the researchers stated that the higher the education level of parents, especially mothers, the greater their ability to absorb the information obtained, especially regarding nutrition in children.…”
Section: 𝐽𝐵 = 𝑛 [contrasting
confidence: 94%
“…That is, the higher percentage of mothers who do not attend formal education, the lower prevalence of stunting in these locations. This is in contrast to research conducted by Azis et al (2021) which showed that risk factors for maternal education affect the incidence of stunting with a risk of 5,5 times. Tatu et al (2021) also analyzed the risk factors associated with the incidence of stunting, and the researchers stated that the higher the education level of parents, especially mothers, the greater their ability to absorb the information obtained, especially regarding nutrition in children.…”
Section: 𝐽𝐵 = 𝑛 [contrasting
confidence: 94%
“…Hal ini sejalan dengan temuan penelitian. 23 Hal ini menunjukkan bahwa hingga 40 orang (62%) wanita hamil tidak berisiko. Kondisi kehamilan ibu dipengaruhi oleh usia ibu pada saat pembuahan karena selain terkait dengan perkembangan organ reproduksi, juga terkait dengan keadaan psikologis, khususnya kesiapan menerima kehamilan.…”
Section: Gambaran Umur Ibu Saat Hamil Tahun 2021 DI Desa Kepyar Kecam...unclassified